1999
DOI: 10.1089/neu.1999.16.299
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Traumatic Brain Injury in Mice Deficient in Intercellular Adhesion Molecule–1: Assessment of Histopathologic and Functional Outcome

Abstract: Intercellular adhesion molecule-1 (ICAM-1) is an adhesion molecule of the immunoglobulin family expressed on endothelial cells that is upregulated in brain as part of the acute inflammatory response to traumatic brain injury (TBI). ICAM-1 mediates neurologic injury in experimental meningitis and stroke; however, its role in the pathogenesis of TBI is unknown. We hypothesized that mutant mice deficient in ICAM-1 (-/-) would have decreased neutrophil accumulation, diminished histologic injury, and improved funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
53
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 42 publications
11
53
0
Order By: Relevance
“…It has previously been shown that treatment with a mAb to CD11d decreases macrophage and neutrophil infiltration into the damaged spinal cord (Mabon et al, 2000;Saville et al, 2004). It has also been demonstrated that endothelial ICAM-1 is expressed on the endothelial surface when exposed to various cytokines and mediates PMNL and endothelial adhesion (Whalen et al, 1999). In addition, the adhesion molecule, E-selectin, is also rapidly expressed on endothelial cells and neutrophils .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…It has previously been shown that treatment with a mAb to CD11d decreases macrophage and neutrophil infiltration into the damaged spinal cord (Mabon et al, 2000;Saville et al, 2004). It has also been demonstrated that endothelial ICAM-1 is expressed on the endothelial surface when exposed to various cytokines and mediates PMNL and endothelial adhesion (Whalen et al, 1999). In addition, the adhesion molecule, E-selectin, is also rapidly expressed on endothelial cells and neutrophils .…”
Section: Discussionmentioning
confidence: 98%
“…Several laboratories have also used transgenic mice that are genetically engineered to overexpress or knockout various genes of interest in the inflammatory cascade (Tehranian et al, 2002;Whalen et al, 1999). For example, Whalen and colleagues (1999) tested mutant mice deficient in ICAM-1 to assess the importance of neutrophil accumulation on the pathogenesis of TBI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inflammatory stress response to TBI includes activation of complement (Kaczorowski et al 1995) and up-regulation of adhesion molecules on the endothelium of cerebral blood vessels (Whalen et al 1999), associated with the accumulation of neutrophils and production of cytokines (Yamasaki et al 1997). Interleukin-8 (IL-8) is considered to be one of the pivotal cytokines in the pathophysiology of TBI.…”
Section: Patientsmentioning
confidence: 99%
“…3 Controlled cortical impact (CCI) has been widely used to model cerebral contusion in mice. [4][5][6][7][8] Because the head is held fixed in a stereotaxic frame, CCI does not impart acceleration/deceleration forces characteristic of concussive TBI, which is characterized by linear or angular acceleration of the head. [9][10][11] We recently published a closed head injury (CHI) model of concussive TBI in mice in which the head freely rotates in the anterior-posterior plane.…”
mentioning
confidence: 99%